THE USE OF PAVEMENT CONDITION INDEX (PCI) AS THE CONSIDERATION OF REHABILITATION PRIORITY - M Akash, Faraj Muftah (Jurnal Teknik Sipil, 2014)
Abstract Highway is one infrastructure that will accelerate an areaâs growth and development and will open social, economic and cultural relationship cros areas Land road is the society vital need in undertaking daily activity therefore the road that can provide good service is very desirable. But, this infrastructure is frequently damaged.this research conducted in Tentara pelajar Street of Surakarta with length of 2,200 km aims to assess the road condition using Pavement Condition Index (PCI) method by dividing road into several segments in 50 m interval. Then, each segment of road was observed and measured to identify the type of damage existing and was assessed according to PCI method. From the result of observation several damages were obtained including alligator cracking, bleeding block cracking, corrugation, longitudinal and transverse cracking, patching and utility cut patching, potholes, Bleeding, Rutting. This damage only and the repair was done based on the type of damage existing in this road, road improvement was done using Component Analysis Method. The hardening material used was LASTON and then necessary expense budget was also estimated the cost of the necessary repairs and improvement in street in Tentara Pelajar 2013 was Rp. 2.066.094.000,00 Planning additional pavement thickness (Overlay) with component analysis methode using Ms.744 Laston obtained (9.5) cm thickness. Keywords: Pavement Condition Index , Budget plane